Kepastian Hukum Restorative Justice Sebagai Suatu Konsep Pemidanaan dalam Hukum Pidana Dihubungkan dengan Pembaharuan Hukum Pidana Indonesia - Ronaldo Maradona Siregar; Joko Sriwidodo; R Lina Sinaulan; Andravirti Karita (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Restorative justice emerges as a sentencing paradigm that shifts orientation from retribution to the restoration of victims’ losses, offenders’ accountability, and social balance. Nevertheless, its implementation in the Indonesian criminal law system still faces fundamental challenges, particularly regarding legal certainty. The fragmentation of sectoral regulations, normative ambiguity, and the contradiction with the retributive paradigm in the old Criminal Code (KUHP) create inconsistencies in practice and weaken legal predictability. This research aims to analyze the gap between the principle of legal certainty (das sollen) and the practice of restorative justice (das sein), as well as to examine the urgency of integrating this concept into the structural sentencing system as part of Indonesian criminal law reform. The study applies a normative juridical method with statutory, conceptual, and case approaches, combined with qualitative analysis of primary and secondary legal materials and selected empirical case studies. The findings reveal that restorative justice has obtained normative legitimacy through several sectoral regulations (Perpol No. 8/2021, Perja No. 15/2020, Perma No. 1/2024), and explicit recognition in the new Criminal Code (Law No. 1/2023). However, its implementation still encounters challenges such as institutional ego, lack of professionalism among law enforcers, and the persistent gap between normative ideals and practical realities. Therefore, integrating restorative justice into the structural sentencing system is an urgent necessity to ensure harmony between justice, legal certainty, and legal utility in the reform of Indonesian criminal law